Kader Posyandu Aktif dan Tidak Berdasarkan Pengetahuan, Sikap, Pendidikan dan Pendapatan - Setyowati, Yuni; Hutagalung, Sihol; Supadi, J (Poltekkes Kemenkes Semarang, 2014)
volunteers are active as Cadre in health center. Some of them are not active, it may be due to the education, knowledge, attitudes, socio-economic and other factors such as motivation, the distance between home and participation in community organizations. In Puskesmas Wonosalam I found 56 posyandu with 284 people in which cadre active 42.6%, 47.2% and 10.2% less active inactive.Objective: to know the difference of knowledge, attitudes, education and income between the active and inactive cadresMethod: The study was a retrospective descriptive analytic study. Sample 29 cadres off as cases and 29 active volunteers as controls. Chi square test was used to determine differences in attitudes and income. To determine differences in knowledge and education using fisher exact test.Results:There is statistically difference in knowledge between the active and inactive volunteers (p = 0.002). There is a difference in attitudes between the active and inactive volunteers (p = 0.000). There is no difference in education between active and inactive volunteers (p = 1.000). There is no difference in income between the active and inactive volunteers (p = 0.791).Conclusion : Refreshing cadres, intensive coaching and support of additional transport and health services for the cadres sholud be added.